Outbreak of Acute Fulminant Myocarditis in Children in Campania Region, Italy: A Case Series - Antonietta Giannattasio; Marco Maglione; Giangiacomo Di Nardo; Giovanni Maria Di Marco; Daria Lauretta; Maria Chiara Carrella; Daniela Furlan; Fabio Savoia; Vincenzo Tipo (Children)
Acute fulminant myocarditis is a rare event in children, accounting for about 10% of all cases of acute myocarditis. Its lack of specific onset patterns and unpredictable evolution make diagnosis and prompt treatment challenging. We observed six cases of fulminant myocarditis admitted to our Pediatric Emergency Unit (Campania region, Sothern Italy) within a very short timeframe (50 days, from July to September 2024). Three of them died, and two are still under treatment in a Pediatric Cardiologic Intensive Care Unit in critical condition. In only one case, cardiac function improved. The described cases were not geographically linked, belonging to different areas of Southern Italy. No common etiological agent was found. Given the relatively low incidence of the condition, the occurrence of six pediatric myocarditis within approximately two months should be considered exceptional. Careful monitoring of further cases in the next few months should be warranted.